The quality of indigenous sheep milk and its paneer and cheese - Gadekar, Yogesh Prabhakar; Shinde, A K; Jairath, Gauri; Bhatt, Randhir S (Indian Journal of Dairy Science, 2019)
Indian sheep produce small quantity of milk to meet their offspring requirement and contribute little to human nutrition. Major portion of sheep milk is consumed as fluid milk and in certain areas convert into ghee and dahi. The present study was undertaken to evaluate the quality of sheep milk and cheese and paneer prepared from it. Sheep milk was collected from experimental animals of Animal Nutrition Division. The pH, titratable acidity and specific density of sheep was 6.13, 0.20 and 1.01 respectively. Sheep milk contained 16.70 % total solids, 5.22% proteins, 7.26% fat, 3.09% lactose and 1.12 % total ash. Effect of two acidulants: acetic and citric acid was evaluated in paneer.Â  The yield of paneer was significantly higher (P